COMPARATIVE STUDY OF LINGUOCULTURAL ASPECTS IN THE FANTASY WORKS OF URSULA K. LE GUIN AND KHUDOYBERDI TOXTABOYEV (International journal of artificial intelligence, 2025)
The article provides a comparative study of the linguistic and cultural features of the fantasy genre in the works of the American writer Ursula K. Le Guin and the Uzbek author Khudoyberdi Toxtaboyev. The study identifies similarities and differences in their artistic representation of imagination, moral development, and symbolic systems. Both writers explore the hero’s journey as a means of personal growth and emphasize the harmony between individual and cosmic balance. The paper concludes that fantasy in their works serves as a linguocultural reflection of moraland philosophical values rooted in distinct national traditions.